THE EFFECT OF SCRAMBLE METHOD ON STUDENTS’ ACHIEVEMENT IN LEARNING VOCABULARY - Susi Rosanti; Iskandar Zulkarnain; Linda Astuti Rangkuti (EXCELLENCE: Journal of English and English Education, 2022)
The objective of this research was to find out the significant effect of the scramble method on students’ achievement in learning vocabulary. The experimental design was used as the research design. The population of this research was taken from the eighth-grade students of SMP Al Washliyah 8 Medan. There were 7 parallel classes with a total number of 231 students. Each class consisted of 33 students. The sample was taken by applying cluster random sampling with the lottery technique. Class VIII1 consisting of 33 students was selected as the experimental group and class VIII3 consisting of 33 students was selected as a control group. The total sample was 66 students. The experimental group was taught by applying the scrambling method, while the control group was taught by applying the conventional method. Multiple-choice tests containing vocabularies were used as the instrument for collecting the data. The mean score of the experimental and control groups were then compared and calculated. The value of both groups then was tested using the t-test formula. It was obtained that that tobserved value was higher than ttable value (7.25 1.66) at a level of significance =0.05 with a degree of freedom df=58. Based on the determined hypothesis, it meant that Ha was accepted and Ho was successfully rejected. Thus, it was concluded that there was a significant effect of the scramble method on students’ achievement in learning vocabulary.